Recyclable zero-valent iron activating peroxymonosulfate synchronously combined with thermal treatment enhances sludge dewaterability by altering physicochemical and biological properties - Li, Yifu (2020)
In this study, zero valent iron (ZVI) activated peroxymonosulfate (PMS) as novel technique (i.e. ZVI-PMS technology) was employed to enhance sludge dewatering. In optimal sludge dewatering conditions of ZVI and KHSO5 dosages, the specific resistance to filtration (SRF) was reduced by 83.6%, which was further decreased to 90.6% after combination of ZVI-PMS with thermal treatment at 50 °C (i.e. ZVI-PMS-T technology). Subsequently, the ESR spectrum and quenching tests demonstrated that OH, rather than SO4-, was predominant radicals in ZVI-PMS conditioning. Thereafter, the variation of physicochemical properties and the distributions and compositions of extracellular polymeric substances (EPS) were further investigated to uncover the influence of these techniques on sludge bulk properties. The results indicated that sludge particles were disintegrated into smaller particles and surface charges were neutralized, sludge flowability were elevated obviously after treatments. In ZVI cycle experiment, the high dewatering efficiency was maintained by ZVI-PMS and ZVI-PMS-T pretreatment.